CATEGORIZING THE MEANINGS OF INTEGRAL HEALTH ASSISTANCE IN LITERATURE OF LATIN AMERICA AND THE CARIBBEAN: A LITERATURE REVIEW (Fiep Bulletin - online, 2013)
The integrality, in the context of the Unified Health System (SUS), can be interpreted in several ways. Within this framework, we aimed at characterizing the articles published on integral health assistance, as addressed to the meanings, focus and form of publication, available in the database of Literature Latin American and Caribbean Health Sciences (LILACS) of the Virtual Library Health (VHL), from January/2005 to December/2007. There were found 156 scientific productions, whose data were categorized based on the text of Pinheiro and Mattos (2001), which classifies the three main directions of integrality, based on "Practice of Integrated Medicine", “Labor Organization "and" Special Policies ", according to year and form of publication. It was identified that concerning the year of publication, 2005 was the period when most were published studies that addressed the integral health assistance (44.2%). According to the type of production, 55.8% were published in the form of abstract and 44.2% as full-text. In relation to the meanings of integral assistance, were identified 44.2% on Integrated Medicine, 39.5% on Labor Organization and 19.9% on Special Policies. From the analysis of scientific production, we saw a lack of work in the area, longing for additional researches that enable accelerating the process of change and awareness of professionals and managers who make the Brazilian public health
Keywords: Integral health assistance; Healthcare system; Literature review as subject.